Diagnosis and epidemiology of Corona Virus (COVID-19) outbreak in Indonesia - Sutaryono, Sutaryono; Andasari, Sholikhah Deti; Kasjono, Heru Subaris (Jurnal Teknologi Laboratorium, 2020)
COVID-19 has experienced an increase in 2,995,758 positive cases and 204,987 deaths, in distribution areas of more than 213 countries. This research using a systematic literature review, policy brief, and internet-based questionnaire with the aim of finding out the diagnosis and epidemiology of Coronavirus (COVID-19) outbreak in Indonesia. The cases in Indonesia have reached 9,771 and killed 784 people, possibly as many as 19 cases are asymptomatic but can be carriers of the virus. The diagnosis is carried out by rapid testing and using a polymerase chain reaction (PCR). Most of the patients diagnosed were aged 30-49 years (38.91%), the highest accompanying diseases were hypertension (34.85%), diabetes mellitus (25.76%), and cardiac disease (17.05%). The most signs and symptoms are that the patient has a cough, shortness of breath, and has a history of internal medicine and fever. Based on sex mostly experienced by men (58.94%) compared to women (41.06%), 60.4% of the community is still active outside the home. The Government of Indonesia is making efforts to reduce the COVID 19 outbreak by implementing a health protocol and a Large-scale Social Restrictions or â€œPembatasan Sosial Berskala Besar (PSBB)â€ policy.